The Impact of Student Development and Its Implications for Education - Andi Tenri Ampa; Nurjannah, Nurjannah; Ratnah S; Andi Tonra Lipu (International Journal of Education, Vocational and Social Science, 2024)
Development is a process of change in growth over time as a function of maturity and interaction with the environment. In other words , development is a functional change that is influenced by the achievement of a level of physical maturity. This development process can be understood by the existence of several principles/laws, in which the principles/laws regulate the entire development process and are certain about something that is in the development process. Thus, these principles must be understood by all education stakeholders, especially for school principals and teachers, because the principles are very urgent in increasing the effectiveness and efficiency of achieving educational goals, including by developing a curriculum or creating learning programs that are appropriate to the developmental stages of student participants